1990
DOI: 10.1002/jmv.1890320204
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B pre‐S1 and pre‐S2 proteins: Clinical significance and relation to hepatitis B virus DNA

Abstract: Pre-S proteins may have an important role in virus assembly and virus entry into the host cell. The presence of pre-S proteins in serum has also been thought to correlate with active viral replication. To investigate whether pre-S proteins in serum might have additional diagnostic and/or predictive value for liver sequelae in HBV infection, sera from six different serological groups of patients with HBV markers (total number 363) and different manifestations of liver histology were examined for the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…In the clinic, the appearance of anti‐preS1 in patients implies a better recovery from AHB . So, we investigated whether there were relationships between anti‐preS1 and reduction of HBV infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinic, the appearance of anti‐preS1 in patients implies a better recovery from AHB . So, we investigated whether there were relationships between anti‐preS1 and reduction of HBV infection.…”
Section: Resultsmentioning
confidence: 99%
“…In the clinic, the appearance of anti-preS1 in patients implies a better recovery from AHB. (25)(26)(27) So, we investigated whether there were relationships between anti-preS1 and reduction of HBV infection. We observed that anti-preS1 was negatively correlated with preS1 antigen (Fig.…”
Section: Pres1 Domain Presents More Immunogenicity Than Hbsag In Clinmentioning
confidence: 99%
“…The epitopes of the two domains are immunogenic in man and mice, and denaturation resistant in Western blots (Milich et al 1985(Milich et al , 1986Neurath et al 1984). The relationship between preS 1/preS2 antigens in serum and the status of viral replication in HBV chronically infected subjects is still controversial (Kuijpers et al 1989;Budkowska et al 1988a;Hu et al 1987;Mondelli et al 1984;Van Ditzhuijsen et al 1990). To gain a better understanding of the serum kinetics of the preS antigens in subjects with chronic HBV infection, we investigated the two antigens in serial serum samples from biopsy-proven chronic active (CAH, three cases) and chronic persistent (CPH, five cases) hepatitis, and from ten asymptomatic carriers, by an enyzme-linked immunosorbent assay (ELISA) employing anti-preS 1 and anti-preS2 monoclonal antibodies (mAb).…”
Section: Introductionmentioning
confidence: 94%
“…The difference between cellulose and high-flux membranes is a greater permeabili ty in the latter to larger molecules, notably in the range of 5,000-50,000 daltons [4], As the molecular weight of H BsAg is 24,000 daltons [5], it is to be expected that it can be demon strated in the dialysate during treatment with high-flux membranes but not with cellulose membranes. The molecular weight of the fulllength HBV-DNA can be estimated to be about 2,000,000 daltons, while an intact H BV virion (Dane particle) has a diameter of 42 nm.…”
mentioning
confidence: 99%